Effect of lactation number on some biochemical parameters in postpartum dairy cows - Taha Burak Elifoglu; Serdal Kurt (Eurasian Journal of Veterinary Sciences)
Aim: This study aimed to investigate the relationship between lactation number, milk yield, and some blood biochemical parameters in dairy cows. Materials and Methods: The material of the study consists of dairy cows (n=60), and three different groups were formed according to the lactation numbers of the cows. Non-lactating heifers were assigned to Group 1 (n=10), 1st and 2nd lactation cows were assigned to Group 2 (n=24), and 3rd and 4th lactation cows were assigned to Group 3 (n=26). The blood total protein, albumin, blood urea nitrogen (BUN) calcium, phosphorus, magnesium, glucose, cholesterol, aspartate transaminase (AST), and gamma-glutamyl transpeptidase (GGT) levels of the cows in the groups were measured. In addition, the milk yields of the groups were compared, and the relationship between these values and milk yield was investigated. Results: Total protein level was higher in the G3, G2 and G1 groups, respectively (p<0.001). Similarly, albumin levels increased significantly in the G3 group compared to the G1 Group (P<0.01). Glucose and cholesterol levels were higher and lower in G1 group compared to other groups (p<0.001; p<0.05), respectively. AST and GGT levels decreased in the G1 group than in the G2 group (p<0.05). Conclusion: In conclusion, the number of lactations in dairy cows significantly affected the biochemical parameters within total protein, albumin, glucose, cholesterol, AST and GGT in dairy cows. These differences were found especially in Group 2 and Group 3, which included multiparous cows, compared to Group 1 (heifers).